Self-healing material for self-driven seawater hydrogen production and preparation method thereof
The self-healing material prepared by the combination of graphene derivatives, organic aqueous solution and borate solution solves the problems of long self-healing time and low efficiency of existing self-healing complexes, and realizes the combination of rapid repair and water desalination and hydrogen production functions at room temperature, with excellent engineering application prospects.
Patent Information
- Application Number
- CN202411762321.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The self-healing time of the existing self-healing complex is too long, and heating conditions are required to achieve the self-healing function. The self-healing efficiency is low and cannot meet the requirements of practical applications.
A self-healing material for self-driven seawater hydrogen production is prepared by ultrasonic dispersion and magnetic stirring using a combination of graphene derivatives, organic aqueous solution and borate solution. This material can quickly repair mechanical damage at room temperature and realize water desalination and instant hydrogen production functions in capacitive deionization devices.
This material has high repair efficiency and speed after mechanical damage, can be repaired by itself at room temperature, has good plasticity and durability, adapts to complex stress and environmental changes, and does not require additional heat or pressure conditions, making it easy to use in practice.
Smart Images

Figure CN119569192A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite materials, in particular to a self-healing material for self-driven seawater hydrogen production and a preparation method thereof. Background Art
[0002] Graphene materials have unique advantages such as high specific surface area, high specific capacitance, and high specific energy. Carbon materials represented by graphene are considered to be one of the materials with full potential. How to prepare efficient graphene materials that can be used in capacitive deionization technology has always been one of the focuses of many researchers.
[0003] A method for preparing a self-healing composite with high tensile stress is disclosed in the publication number CN111154207A. The material is made of graphene oxide and polyvinyl alcohol by first cyclic freezing and thawing and then drying. The composite uses the rich oxygen-containing group characteristics of graphene oxide to increase the hydrogen bonding sites of the composite, forming a dynamic reversible hydrogen bonding network to give the composite self-healing properties, while also enhancing the mechanical properties of the composite. However, the self-healing time of the self-healing composite prepared by the patent is too long, and heating conditions are required to achieve the self-healing function. The efficiency of its self-healing is low and cannot meet the requirements of practical applications for self-healing materials.
[0004] To this end, those skilled in the art have proposed a self-healing material for self-driven seawater hydrogen production and a preparation method thereof to solve the problems raised by the background technology. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a self-healing material for self-driven seawater hydrogen production and a preparation method thereof to solve the problems in the prior art.
[0006] A self-healing material for self-driven seawater hydrogen production comprises the following component materials: a graphene derivative, an organic aqueous solution and a borate solution.
[0007] Preferably, the graphene derivative includes one or more of graphene oxide, reduced graphene oxide, single-layer graphene, and multi-layer graphene.
[0008] Preferably, the organic aqueous solution includes a solution of one or more of polyvinyl alcohol, polyethylene glycol, carboxypropyl methylcellulose, polypropylene alcohol mixed with deionized water.
[0009] Preferably, the borate solution includes a solution of one or more of sodium borate, lithium borate, potassium borate, calcium borate, magnesium borate, sodium metaborate, lithium metaborate, potassium metaborate, calcium metaborate, and magnesium metaborate mixed with deionized water.
[0010] A method for preparing a self-healing material for self-driven seawater hydrogen production comprises the following steps:
[0011] S1, mixing the organic matter with deionized water, using ultrasonic dispersion treatment or stirring to fully dissolve the organic matter until there are no particles, and obtaining an organic solution for standby use;
[0012] S2, adding the graphene derivative to the organic solution in batches and adding the mixture to a magnetic stirrer for stirring, so that the graphene derivative and the organic solution are fully mixed and uniformly until there is no particle and the mixture is thick, and the mixture is used for standby;
[0013] S3. Adding a borate solution into the mixture and stirring again to obtain a graphene composite material.
[0014] Preferably, in step S1, the mass percentage concentration of organic matter in the organic solution is 0.5-20%, the ultrasonic dispersion time is 5-200 min, and the ultrasonic dispersion power is 10w-1000w.
[0015] Preferably, in step S2, the mass ratio of the added graphene derivative to the organic matter is 1%-99%, the speed of the magnetic stirrer is controlled at 50-2000 r / min, the stirring temperature is controlled at 20-120° C., and the stirring time is controlled at 5-200 min.
[0016] Preferably, in step S3, the mass concentration percentage of the borate solution is 0.1%-20%, and the volume of the added borate solution accounts for 0.5%-10% of the volume of the organic solution.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The preparation method of the present invention is simple and cost-controllable. The prepared material has high repair efficiency and speed after mechanical damage, and can quickly recover to the original mechanical properties after damage; at the same time, it has good plasticity and durability, good stability, and can adapt to complex stress and environmental changes. The self-healing process does not require additional special conditions such as heat and pressure, and can self-repair mechanical damage such as fracture at room temperature, which is convenient for practical application and has good engineering application prospects. At the same time, the 3D printed self-healing material is applied to a capacitive deionization device, which can realize the functions of water desalination and instant hydrogen production under power-on conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 A diagram showing the self-healing process of the 3D printed self-healing graphene composite material prepared in Experimental Example 1 of the present invention;
[0020] Figure 2A demonstration diagram of the 3D printed self-healing graphene composite material prepared in Experimental Example 1 of the present invention being applied to water treatment in a capacitive deionization device and a desalinated water electrolysis hydrogen production device;
[0021] Figure 3 This is a graph showing the rate of hydrogen production by electrolysis of desalinated water in Experimental Example 1 of the present invention;
[0022] Figure 4 This is a SEM image of the 3D printed self-healing graphene composite material prepared in Experimental Example 1 of the present invention;
[0023] Figure 5 This is a SEM image of the 3D printed self-healing graphene composite material prepared in Experimental Example 2 of the present invention;
[0024] Figure 6 This is a SEM image of the 3D printed self-healing graphene composite material prepared in Experimental Example 3 of the present invention;
[0025] Figure 7 This is a Raman spectrum of the 3D printed self-healing graphene composite material prepared in Experimental Example 1 of the present invention;
[0026] Figure 8 This is a Raman spectrum of the 3D printed self-healing graphene composite material prepared in Experimental Example 2 of the present invention;
[0027] Fig. 9 This is a Raman spectrum of the 3D printed self-healing graphene composite material prepared in Experimental Example 3 of the present invention. DETAILED DESCRIPTION
[0028] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0029] Embodiment 1: The present invention provides a self-healing material for self-driven seawater hydrogen production, comprising the following component materials: a graphene derivative, an organic aqueous solution, and a borate solution.
[0030] Furthermore, the graphene derivative includes one or more of graphene oxide, reduced graphene oxide, single-layer graphene, and multi-layer graphene.
[0031] Among them, graphene oxide has good hydrophilicity and dispersibility, which helps the material to be better dispersed and stabilized in water. At the same time, it contains rich functional groups, such as hydroxyl groups, carboxyl groups, etc., which provides more possibilities for combination with other ingredients.
[0032] Reducing graphene oxide can improve the conductivity of the material, which is crucial for electron transport in the process of self-driven seawater hydrogen production.
[0033] Single-layer graphene and multi-layer graphene can provide extremely high specific surface area, which is beneficial to increase reaction sites and improve hydrogen production efficiency.
[0034] Furthermore, the organic aqueous solution includes a solution formed by mixing one or more of polyvinyl alcohol, polyethylene glycol, carboxypropyl methylcellulose, and polypropylene alcohol with deionized water.
[0035] Among them, polyvinyl alcohol and polyethylene glycol are high molecular polymers that can form viscous solutions, which are helpful for the formation and stabilization of self-healing materials, provide good water retention and lubricity, and help the dispersion and reaction of materials in seawater.
[0036] Carboxypropyl methylcellulose and polypropylene alcohol contain functional groups such as carboxyl groups, which can interact with graphene derivatives and components in borate solutions to enhance the cohesion of the material.
[0037] Furthermore, the borate solution includes a solution formed by mixing one or more of sodium borate, lithium borate, potassium borate, calcium borate, magnesium borate, sodium metaborate, lithium metaborate, potassium metaborate, calcium metaborate, and magnesium metaborate with deionized water.
[0038] Among them, sodium borate, lithium borate, potassium borate, calcium borate and magnesium borate can form stable ion pairs in solution, which helps to maintain the electrolyte balance of the material.
[0039] Sodium metaborate, lithium metaborate, potassium metaborate, calcium metaborate, and magnesium metaborate can provide additional boron sources, help form a denser borate network structure, and enhance the self-healing ability of the material. By adjusting the type and concentration of the borate, the hydrogen production performance and stability of the material can be optimized.
[0040] Embodiment 2: This embodiment is basically the same as the previous embodiment, except that a method for preparing a self-healing material for self-driven seawater hydrogen production comprises the following steps:
[0041] S1, mixing the organic matter with deionized water, using ultrasonic dispersion treatment or stirring to fully dissolve the organic matter until there are no particles, and obtaining an organic solution for standby use;
[0042] Among them, ultrasonic dispersion treatment or stirring is used to ensure that the organic matter is completely dissolved in deionized water to form a uniform organic solution, which is helpful for better mixing with other materials in subsequent steps and improving the overall uniformity and performance of the material. The use of deionized water can reduce the impact of impurities in the water on the material properties and ensure that the prepared self-healing material has higher purity and stability.
[0043] S2, adding the graphene derivative to the organic solution in batches and adding the mixture to a magnetic stirrer for stirring, so that the graphene derivative and the organic solution are fully mixed and uniformly until there is no particle and the mixture is thick, and the mixture is used for standby;
[0044] Among them, graphene derivatives have excellent conductivity, mechanical strength and thermal stability. Mixing them with organic solutions can significantly improve the overall performance of self-healing materials, such as conductivity, toughness and corrosion resistance. By adding them in batches and magnetic stirring, the graphene derivatives can be evenly dispersed in the organic solution to avoid agglomeration, thereby improving the uniformity and consistency of the material.
[0045] S3. Adding a borate solution into the mixture and stirring again to obtain a graphene composite material.
[0046] Among them, the addition of borates can give self-healing materials unique self-healing abilities. When the material is damaged, borates can prompt the chemical bonds inside the material to reconnect, thereby repairing the damage and restoring the material's performance. Borates may form stable chemical bonds with graphene derivatives and organic matter, improving the chemical stability and durability of the material, enabling it to maintain good performance even in harsh environments.
[0047] Furthermore, in step S1, the mass percentage concentration of organic matter in the organic solution is 0.5-20%, the ultrasonic dispersion time is 5-200 min, and the ultrasonic dispersion power is 10w-1000w.
[0048] The mass percentage concentration of organic matter is 0.5-20%. This concentration range ensures that organic matter can be fully dissolved in deionized water to form a stable solution. Too low a concentration may lead to uneven dispersion of organic matter, while too high a concentration may increase the viscosity of the solution and affect subsequent processing. By adjusting the concentration, the fluidity and mixing effect of the solution can be optimized.
[0049] Controlling the time and temperature of ultrasonic dispersion can effectively break up the agglomeration of organic particles and make them more evenly dispersed in deionized water. Properly extending the ultrasonic time and increasing the power can enhance the dispersion effect, but too long a time and too high a power may also cause the solution temperature to rise, affecting the stability of the organic matter.
[0050] Furthermore, in step S2, the mass ratio of the added graphene derivative to the organic matter is 1%-99%, the speed of the magnetic stirrer is controlled at 50-2000 r / min, the stirring temperature is controlled at 20-120° C., and the stirring time is controlled at 5-200 min.
[0051] Among them, the mass ratio of added graphene derivatives to the mass ratio of organic matter is 1%-99%. This ratio range allows the content of graphene derivatives to be adjusted according to specific needs, thereby controlling the conductivity, mechanical strength and other properties of the material. The speed, temperature and time control of the magnetic stirrer can ensure that the graphene derivatives can be evenly dispersed in the organic solution. The appropriate speed and temperature can accelerate the mixing process and improve the mixing efficiency, while the appropriate stirring time ensures the adequacy of the mixing. By adjusting these parameters, the mixing effect can be optimized and the agglomeration and precipitation of the graphene derivatives can be avoided.
[0052] Furthermore, in step S3, the mass concentration percentage of the borate solution is 0.1%-20%, and the volume of the added borate solution accounts for 0.5%-10% of the volume of the organic solution.
[0053] The mass concentration percentage of the borate solution is 0.1%-20%. This concentration range allows the borate content to be adjusted according to specific needs, thereby controlling the self-healing ability and other related properties of the material. Lower concentrations may be suitable for applications that require lower self-healing rates, while higher concentrations may be used in situations that require faster self-healing rates. The volume of the borate solution accounts for 0.5%-10% of the volume of the organic solution. By controlling the amount of borate solution added, the performance of the self-healing material can be precisely adjusted. Too little addition may result in insufficient self-healing ability, while too much addition may affect the overall performance and stability of the material. This range provides sufficient flexibility to optimize the performance of the material.
[0054] From the above, it can be seen that by setting parameters to ensure that the self-healing material has excellent performance, stability and preparation efficiency, and by precisely controlling these parameters, high-performance self-healing materials that meet specific needs can be prepared.
[0055] Experimental Example 1:
[0056] First, 5 g of polyvinyl alcohol powder was weighed and added to 95 ml of deionized water. After ultrasonic dispersion for 10 minutes at an ultrasonic power of 100 W, the mixture was added to a stirrer and stirred for 30 minutes at a stirring temperature of 95 ° C to fully dissolve the mixture. The mixture was then placed at room temperature to fully cool to obtain a polyvinyl alcohol solution. Then, 0.5 g of graphene oxide was weighed and added to 50 ml of deionized water. l polyvinyl alcohol solution, ultrasonic power 100w, ultrasonic treatment for 30 minutes to make it evenly dispersed, then added into a magnetic stirrer and stirred for 60 minutes, the stirring temperature is 25 ° C, so that the graphene oxide is fully dispersed in the polyvinyl alcohol solution into a viscous and non-granular state, and finally 0.5 ml of a sodium metaborate solution with a mass percentage concentration of 1% is added dropwise. After stirring for 5 minutes, the material is loaded into a 3D printer, the air pressure is controlled to 0.1-6Mpa, and the discharge rate is controlled to 1-100mm / s to prepare a 3D printed self-healing graphene composite material. The 3D printed self-healing graphene composite material printed by the 3D printer is loaded into a capacitive deionization device, and untreated water is passed at a rate of 600ml per minute. Under the condition of power on, the water quality reaches the conditions for hydrogen production by electrolysis of water through the adsorption of the 3D printed self-healing graphene composite material, and the treated water is passed into the water electrolysis hydrogen production device to realize the hydrogen production function.
[0057] Performance Test:
[0058] The self-healing properties of the material were tested. First, the tensile strength of the material was measured to be 96 MPa and the elongation at break was 42.7%. Figure 1 As shown in the figure, it can be seen that after the material is cut, it can be placed at room temperature for 30 seconds, and the fracture surface can successfully achieve self-healing, and no obvious fracture occurs after stretching, showing the excellent self-healing performance of the material. After self-healing after fracture, the 3D printed self-healing graphene composite material was measured again, and its tensile strength was 89Mpa and the elongation at break was 39.1%. Figure 4 It can be seen that the graphene microscopic surface morphology of the material after short-term self-healing is well maintained; Figure 7 As shown in the figure, the Raman characteristic peaks of the self-healed material are consistent with the Raman characteristic peaks of graphene, indicating that the self-healing process of the material will not affect the structure of the graphene inside it. Figure 2 and Figure 3 It can be seen that the desalinated water that has been adsorbed and desalinated by this material can be electrolyzed to produce hydrogen, and the hydrogen production can reach 400 ml per minute.
[0059] Experimental Example 2:
[0060] First, 3 g of polyvinyl alcohol powder was weighed and added to 97 ml of deionized water. After ultrasonic dispersion was performed at an ultrasonic power of 100 w for 10 minutes, a magnetic stirrer was added and stirred on a magnetic stirrer for 30 minutes at a stirring temperature of 95° C. to fully dissolve the powder. After that, the powder was placed at room temperature to fully cool the powder to obtain a polyvinyl alcohol solution. Then, 0.5 g of graphene oxide was weighed and added to 50 ml of the polyvinyl alcohol solution. After ultrasonic treatment was performed at an ultrasonic power of 100 w for 30 minutes to uniformly disperse the powder. Then, a magnetic stirrer was added and stirred on a magnetic stirrer for 60 minutes at a stirring temperature of 25° C. to fully disperse the graphene oxide in the polyvinyl alcohol solution into a viscous liquid. The method is non-granular; finally, 0.5 ml of a sodium metaborate solution with a mass percentage concentration of 1% is added dropwise, and after stirring for 5 minutes, the material is loaded into a 3D printer, the air pressure is controlled to be 0.1-6 Mpa, and the discharge rate is controlled to be 1-100 mm / s, so as to prepare a 3D printed self-healing graphene composite material, and the 3D printed self-healing graphene composite material printed by the 3D printer is loaded into a capacitive deionization device, and untreated water is introduced at a rate of 600 ml per minute. Under the condition of power on, the water quality reaches the conditions for hydrogen production by electrolysis of water through the adsorption of the 3D printed self-healing graphene composite material, and the treated water is introduced into the hydrogen production device by electrolysis of water to realize the hydrogen production function.
[0061] Performance Test:
[0062] The mechanical tensile properties of the material were tested. First, the tensile strength of the material was measured to be 78Mpa, and the elongation at break was 35.8%. Then it was cut and left at room temperature for one to two minutes, and the fracture was able to successfully self-heal, and no obvious fracture occurred after stretching. After repeated stretching for three times, it was still able to achieve self-healing function after being left for several minutes. At the same time, the tensile strength of the material after repeated stretching and fracture healing was measured to be 71Mpa, and the elongation at break was 33.6%. This shows the excellent self-healing performance of the material. Figure 5 This is the SEM image of the surface morphology of the material after multiple cutting and repair. Figure 8 This is the Raman spectrum of the material after multiple cuts and repairs. The graphene surface morphology and structure of the self-healed material are well maintained, and the Raman characteristic peaks of the self-healed material are consistent with the Raman characteristic peaks of graphene, indicating that the self-healing process of the material will not affect the structure of its internal graphene and the healing stability of the material is very good.
[0063] Experimental Example 3:
[0064] First, 10 g of polyvinyl alcohol powder was weighed and added to 90 ml of deionized water. After ultrasonic dispersion was performed at an ultrasonic power of 100 W for 10 minutes, a magnetic stirrer was added and stirred on a magnetic stirrer for 30 minutes at a stirring temperature of 95°C to fully dissolve the powder. The powder was then placed at room temperature to fully cool to obtain a polyvinyl alcohol solution. Then, 0.5 g of graphene oxide was weighed and added to 50 ml of the polyvinyl alcohol solution. The powder was ultrasonically treated at an ultrasonic power of 100 W for 30 minutes to uniformly disperse the powder. Then, a magnetic stirrer was added and stirred on a magnetic stirrer for 30 minutes. The mixture was stirred for 60 minutes at a stirring temperature of 25° C., so that the graphene oxide was fully dispersed in the polyvinyl alcohol solution into a viscous and particle-free state; finally, 0.5 ml of a sodium metaborate solution with a mass percentage concentration of 1% was added dropwise, and after stirring for 5 minutes, the material was loaded into a 3D printer, the air pressure was controlled to be 0.1-6 MPa, and the discharge rate was controlled to be 1-100 mm / s to prepare a 3D printed self-healing graphene composite material, and the 3D printed self-healing graphene composite material printed by the 3D printer was loaded into a capacitive deionization device, and untreated water was introduced at a rate of 600 ml per minute. Under the condition of power on, the water quality reached the condition of hydrogen production by electrolysis of water through the adsorption of the 3D printed self-healing graphene composite material, and the treated water was introduced into the water electrolysis hydrogen production device to realize the hydrogen production function.
[0065] Performance Testing:
[0066] The self-healing performance of the material was tested. First, the tensile strength of the material was measured to be 107.2Mpa, and the elongation at break was 44.3%. Then it was cut and placed at room temperature for 30 seconds. The fracture was able to successfully self-repair, and no obvious fracture occurred after stretching. It was repeatedly stretched three times until it broke and placed for 30 seconds. It was still able to self-heal. At the same time, the tensile strength of the material after self-healing was measured to be 95.1Mpa, and the elongation at break was 40.32%. This shows the excellent self-healing performance of the material. Figure 6 This is the SEM image of the surface morphology of the material healed after multiple cuts. Fig. 9 This is the Raman spectrum of the material that healed after multiple cuts. The graphene surface morphology and structure of the self-healed material are well maintained, and the Raman characteristic peaks of the self-healed material are consistent with the Raman characteristic peaks of graphene, indicating that the self-healing process of the material will not affect the structure of the internal graphene, and the 3D printed self-healing graphene composite material can maintain good self-healing stability.
[0067] From the above, it can be seen that the preparation method of the present invention is simple and cost-controllable. The prepared material has high repair efficiency and speed after mechanical damage, and can quickly recover to the original mechanical properties after damage; at the same time, it has good plasticity and durability, good stability, and can adapt to complex stress and environmental changes. The self-healing process does not require additional special conditions such as heat and pressure, and can self-repair mechanical damage such as fracture at room temperature, which is convenient for practical application and has good engineering application prospects. The 3D printed self-healing material is applied to a capacitive deionization device, which can realize the functions of water desalination and instant hydrogen production under power-on conditions.
[0068] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A self-healing material for self-driven seawater hydrogen production, characterized in that: The material composition includes the following components: graphene derivatives, organic aqueous solution and borate solution.
2. A self-healing material for self-driven seawater hydrogen production as claimed in claim 1, characterized in that: The graphene derivative includes one or more of graphene oxide, reduced graphene oxide, single-layer graphene, and multi-layer graphene.
3. A self-healing material for self-driven seawater hydrogen production as claimed in claim 1, characterized in that: The organic aqueous solution includes a solution of one or more of polyvinyl alcohol, polyethylene glycol, carboxypropyl methylcellulose, and polypropylene alcohol mixed with deionized water.
4. A self-healing material for self-driven seawater hydrogen production as claimed in claim 1, characterized in that: The borate solution includes a solution of one or more of sodium borate, lithium borate, potassium borate, calcium borate, magnesium borate, sodium metaborate, lithium metaborate, potassium metaborate, calcium metaborate, and magnesium metaborate mixed with deionized water.
5. A method for preparing a self-healing material for self-driven seawater hydrogen production, according to any one of claims 1 to 4, wherein: The steps include: S1, mixing the organic matter with deionized water, using ultrasonic dispersion treatment or stirring to fully dissolve the organic matter until there are no particles, and obtaining an organic solution for standby use; S2, adding the graphene derivative to the organic solution in batches and adding the mixture to a magnetic stirrer for stirring, so that the graphene derivative and the organic solution are fully mixed and uniformly until there is no particle and the mixture is thick, and the mixture is used for standby; S3. Adding a borate solution into the mixture and stirring again to obtain a graphene composite material.
6. A method for preparing a self-healing material for self-driven seawater hydrogen production as claimed in claim 5, characterized in that: In step S1, the mass percentage concentration of organic matter in the organic solution is 0.5-20%, the ultrasonic dispersion time is 5-200 minutes, and the ultrasonic dispersion power is 10w-1000w.
7. A method for preparing a self-healing material for self-driven seawater hydrogen production as claimed in claim 5, characterized in that: In step S2, the mass ratio of the added graphene derivative to the organic matter is 1%-99%, the speed of the magnetic stirrer is controlled at 50-2000 r / min, the stirring temperature is controlled at 20-120° C., and the stirring time is controlled at 5-200 min.
8. A method for preparing a self-healing material for self-driven seawater hydrogen production as claimed in claim 5, characterized in that: In step S3, the mass concentration percentage of the borate solution is 0.1%-20%, and the volume of the added borate solution accounts for 0.5%-10% of the volume of the organic solution.
Citation Information
Patent Citations
Preparation method of high-tensile-stress self-repairing compound
CN111154207A
Composite nanofiber, preparation method and application thereof, wide-temperature-range anti-wear self-repairing lubricating grease and preparation method of wide-temperature-range anti-wear self-repairing lubricating grease
CN115746936A
Self-repairing graphene composite material and preparation method thereof
CN116715929A
Self-repairing anti-dendritic lithium battery diaphragm and preparation method thereof
CN117423955A
Self-healing aerogel
WO2022016713A1